Applied ethology management methods for resilient calves - Mazzardo Bortoluzzi, Eduarda (Kansas State University, 2019)
Behaviors and immune-measures can be used as indicators of animal health and welfare. Measures of passive immune transfer and solid-feed intake often are used to gauge weaning readiness for dairy cattle. Technological improvements in an automated collection of behavioral data make it feasible to replace invasive techniques and time-consuming measures. This thesis will introduce studies that used applied ethology for beef and dairy calves as indicators of resilience, passive immune transfer, and weaning readiness. Study 1 was conducted to determine if automated data collection of stand-lie behaviors and environmental enrichment device (EED) usage could detect differences among four different weaning protocols for male Holstein calves. For first treatment, MOD-STEP calves were fed 0.66 kg/d of milk replacer (MR) and were step-down weaned by age 6 weeks (PM milk replacer feeding was withdrawn 1 wk before weaning, and last milk replacer feeding was withdrawn at age 42 d). For the remaining 3 treatments, calves were fed higher planes of milk replacer (1.09 kg/d MR). Treatments were: 1) Step-down weaned (HI-STEP) at age 6 wk; 2) Step-down weaned at age 8 wk (HI-LATE), or; 3) Gradually weaned by age 8 wk (HI-GRAD). From age 6 d to 1 wk after weaning, calves were provided an environmental enrichment device (EED), which was a dummy nipple attached to a bottle and holder. In addition, calves had an accelerometer attached to their rear leg to detect stand-lie data before, during, and after weaning. Results showed that calves fed HI-milk replacer (HI-STEP and HI-GRAD) used EED with more frequency and spent less time resting. This study confirms that applied ethology can be used as an indicator of "weaning readiness" in dairy calves. Study 2 was conducted to identify and refine directly observed calf nursing behaviors and better understand their relationships to physiological biomarkers in dams and calves. Data from 59 two-year-old Angus-cross heifers' body weight and blood were collected during day one of the study. Heifers were then moved to a maternity pasture where trained observers monitored calving progression. Times were collected for each calf’s: birth (calf on the ground); stand (all four limbs upright for > 5 seconds); first-suckle (mouth contact with any teat); and each teat during 24 hr after birth. After the 24 h observation period, body weights were measured, and blood was collected and used to measure complete blood counts. Plasma was analyzed for: immunoglobulins G1 and M, total plasma protein (TPP), cortisol, and haptoglobin. Calves were divided in two groups using a threshold of 10 g/L of IgG. Calves that failed to acquire passive immune transfer required more time to stand up and to start suckling. Correlations were found between TPP and latency to stand and to first suckle, indicating that precocious behaviors can be used to predict passive immune transfer in neonatal calves. Applied ethology tools can be used to refine and replace invasive and time-consuming measures, such as blood collection and solid feed weigh back. Ethology also may be used guide calf raisers' management decisions.
Keywords: Neonatal; Weaning; Sucking behaviors; Lie behavior; Passive immune transfer; Colostrum